Clinical characterisation of hypertrophic cardiomyopathy caused by MYH7 gene variants in children. (14th October 2021) - Kadirrajah, V; Acquaah, V; Norrish, G; Field, E; Dady, K; Cervi, E; Kaski, J P
Abstract: Background: Variants in the cardiac Beta Myosin Heavy chain 7 gene (MYH7) are a common cause of hypertrophic cardiomyopathy (HCM) in adults, but their role in paediatric-onset HCM has not been systematically characterised. This study aims to describe the presentation, clinical characteristics and outcomes of childhood HCM secondary to disease-causing MYH7 variants. Methods: Retrospective, longitudinal, data from 70 individuals meeting diagnostic criteria for HCM under the age of 18 years with disease-causing MYH7 variants from a single specialist centre (1991–2019) were collected. A Major Adverse Cardiac Event was defined as sudden cardiac death (SCD), heart failure-related death, cardiac transplantation, haemodynamically-compromising sustained ventricular arrhythmia or appropriate implantable cardioverter defibrillator (ICD) therapy. Results: Median age at diagnosis was 9.2 years (IQR 4.2–13.3 years); 47 patients (67.1%) were less than 12 years and 7 (10.0%) were under the age of 1 at diagnosis. Twenty-two patients (31.4%) were probands. MYH7 variants were missense (n=67) or truncating (n=1). Reason for presentation were: family screening (n=45, 64.3%); cardiac symptoms (n=12, 17.1%); incidental finding (n=11, 15.7%); and out of hospital cardiac arrest (n=2, 2.9%). At baseline, mean maximum left ventricular wall thickness (MLVWT) z-score was 9.6 (±5.8), 11 patients (15.7%) had resting left ventricular outflow tract obstruction (left ventricular outflow tract gradient ≥30mmHg). Baseline phenotype did not significantly differ between probands and non-probands (MLVWT Z score 11.9 (±4.5) vs 8.5 (±6.1), p-value 0.0675). Over a median follow up of 3.6 years (IQR 1.8–7.9 years), 10 patients (14.3%) underwent a left ventricular septal myectomy at a median age 6.4 years (IQR 3.4–12.1 years) and 27 (38.6%) had an implantable cardioverter defibrillator (ICD) for primary (n=24, 34.3%) or secondary (n=3, 4.3%) prevention. Three patients (4.3%) died (SCD, n=1; heart-failure related, n=1; non-cardiac, n=1) and 3 (4.3%) underwent cardiac transplantation. Ten patients (14.3%) experienced a MACE. Patients who experienced a MACE were more likely to be probands [n= 6 (60.0%) vs n=16 (26.7%); p=0.036] but did not differ in terms of baseline phenotype (p=0.134). Conclusion: MYH7 variants can cause infantile and childhood-onset disease, which is associated with significant early cardiac morbidity and mortality. Adverse outcomes were more common in those presenting as probands. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Medical Research Council, Great Ormond Street Hospital charity.